ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KESEHATAN KOPERASI MENURUT PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTRIAN KOPERASI DAN USAHA KECIL DAN MENENGAH NOMOR 06/Per/Dep.6/IV/2016 PADA KOPERASI GURU BINA MANDIRI - Sandi Yuda, Mulfi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
This study analyzes the financial statements and health level of the Guru Bina Mandiri savings and loan cooperative. This research uses ex post facto methods. Data is obtained through financial statement documents such as balance sheets, income statements (SHU), and income statements. The indicators used to assess the health of cooperatives refer to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises number 06 / Per / Dep.6 / IV / 2016. In this study, the results obtained for the 2023 Bina Mandiri Teacher Cooperative got a score of 42.45 at <51.00 with the predicate in special supervision.